Characteristic of Shallow Subsurface Quaternary Sediment in Nongsa Isle, Part of Putri Islands, Batam, Based on Georadar Data Interpretation - Undang Hernawan; Nineu Yayu Geurhaneu; Muhammad Zulfikar (Marine Geological Institute of Indonesia, 2019)
Nongsa Isle belongs to Putri Islands in Batam, is the outermost island that need to be protected either from natural hazards and anthropogenic factor. Therefore, this study was conducted by performing Ground Penetrating Radar analysis, in order to understand the geological condition particularly sedimentology and its process. We used Sirveyor 20 GPR equipment type with MLF antenna frequency 40 Mhz and Radan 5 as processing software, which include time zero correction, spatial filter, deconvolution, migration and adjustment of amplitude and signal gain. Data interpretation was conducted based on radar facies methodology that describes georadar image/radargram. The study result showed differences of sedimentary facies based on three differences of radar facies units, with the first layer (unit 1) is the youngest unit has thicknesses ranging from 3.5 – 5 m that characterized by parallel, strong reflector, high amplitude and continuous reflector configurations, unit 2 from 5 – 11 meter of depth, indicates parallel reflector pattern with medium-high amplitude and continuous, and unit 3 which is the oldest unit with thickness until penetration limit (11 – 20 m), characterized by a configuration of sub parallel – hummocky reflectors that are undulating, low-medium amplitude reflectors. Based on radar facies characteristics such as reflector configuration, reflection amplitude, and reflection continuity, the differencies of depositional facies are changes from fluvial – coastal plain.